(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Constraints during the Communist Regime, as a Price for the Granted Religious Freedom, observed in the Life of a neo-Protestant Denomination in Romania.At the end of the Second World War, the neo-Protestant confessions wanted and asked the state to recognize the right to worship alongside the other already recognized religions. The granting of this right was achieved at the price of certain conditions that were imposed. We will look at how some of these influenced the Pentecostal denomination.